THE APPLICATION OF STRENGTHS-BASED COUNSELING TO ENHANCE THE RESILIENCE OF PARENTS OF CHILDREN WITH SPECIAL NEEDS - Nurul Hidayati; Amelia Rizky Idhartono; Ana Rafikayati; Reza Rachmadtullah (Jurnal Konseling Pendidikan Islam, 2026)
Families with children with special needs (ABK) face complex relationships among family members. This often becomes a stressor that impacts parental resilience. Resilience is a form of ability of parents with special needs to overcome difficulties or problems caused by the presence and condition of children with special needs. Strength-Based Counseling is a counseling approach that uses a positive psychology approach and emphasizes the strengths of an individual or group of people. Strength-based counseling is considered more appropriate for today's era, due to its practicality and emphasis on positive aspects. This research is a case study, with research methods including observation, and interviews. Resilience is a crucial aspect of an individual's life, especially for parents of children with special needs. This study demonstrates that through the application of strengths-based counseling, parents of children with special needs gain reinforcement in their protective factors, thereby increasing their resilience. The results indicate that the use of strengths-based counseling can make parents of children with special needs feel better understood, more confident, and receive help and support, thereby increasing their resilience.